ANALYSIS OF BREEDER MOTIVATION IN RAISING MADURA CATTLE AT WEST WARU VILLAGE, WARU DISTRICT, PAMEKASAN REGENCY - Melisa Hayatul Maryam; Teti Sugiarti; Taufik Rizal Dwi Adi Nugroho (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
The motivation of farmers to raise cattle in Waru Barat Village is only done as a side business and fill their spare time for useful activities, because each farmer has a specific goal of raising cattle according to their respective needs and hobbies. The aims of this study were (1) to analyze the characteristics of farmers (2) to analyze the level of motivation of farmers in raising cattle (3) to analyze the effect of farmer characteristics on the motivation of farmers to raise cattle. The research location was chosen deliberately, namely in the Waru Barat Village, the sample used was 43 respondents. Data were collected by simple random sampling technique, then quantitative descriptive analysis and statistical analysis were performed using multiple linear regression. The results showed that the average age of the breeder was 30-40 years, elementary school education level, experience raising 21-30 years, the number of cattle kept 1-3 heads, the number of family dependents as many as 3-4 people, with the level of knowledge about AI technology within the medium category, and the intensity of communication in the high category, the level of motivation of farmers is in the very high category, the motivation comes from the motivation of raising livestock for the needs of existence, connection, development and entertainment. The characteristics of breeders that have a significant effect on motivation are the number of cattle kept, the number of dependents in the family, and the intensity of communication.